2013
DOI: 10.2991/asshm-13.2013.127
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Poverty and Socio-demographic Characteristics of Poor Households: A Case Study in Kelantan, Malaysia

Abstract: Poverty is a complex and comprehensive phenomenon and covers many dimensions of human and social behaviour. Therefore, poverty reduction has become the most important issue in the development policies of almost all the countries including Malaysia. Poverty in Malaysia has generally been perceived as a rural problem since poverty is much higher in rural areas of the country. This study aims to identify the socio-demographic factors that affect the levels of poverty among the households in Kelantan, Malaysia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Similarly, Majid et al (2016) found that areas with highest poverty concentrations were in northeast Kelantan and Hulu Terengganu while Klang valley had a low incidence of poverty. Siwar et al (2016) in their study found that Kelantan proportion of the poor households in urban areas was 39.11% and rural areas equal to 30.18%. The finding indicates that the incidence of poverty was higher in urban areas as compared to rural areas of the state.…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, Majid et al (2016) found that areas with highest poverty concentrations were in northeast Kelantan and Hulu Terengganu while Klang valley had a low incidence of poverty. Siwar et al (2016) in their study found that Kelantan proportion of the poor households in urban areas was 39.11% and rural areas equal to 30.18%. The finding indicates that the incidence of poverty was higher in urban areas as compared to rural areas of the state.…”
Section: Introductionmentioning
confidence: 90%
“…Poverty in Malaysia is defined as having insufficient income to purchase a minimum basket of food to maintain household members in good health and they do not have access to other basic needs such as health care, education, house rental, and clothing (Siwar et al 2013).…”
Section: Awqaf and Zakat: Tools Of Poverty Alleviationmentioning
confidence: 99%